Oil palm microfiber-reinforced handsheet-molded thermoplastic green composites for sustainable packaging applications. Issue 4 (November 2019) - Hermawan, D; Hazwan, Che Mohamad; Owolabi, FAT; Gopakumar, Deepu A; Hasan, M; Rizal, Samsul; Sri Aprilla, NA; Mohamed, AR; Khalil, HPS Abdul
The forestry and agricultural market have been perceiving outstanding growth due to the advantages of green composites, such as cost effective in nature, environment friendly, excellent mechanical properties, and so on. Various researchers had studied the reinforcement efficiency of various natural fibers in the diverse polymer matrices. Herein, we reported the characterization of microfiber handsheet-molded thermoplastic green composites developed from the combination of oil palm empty fruit bunch (OPEFB)-based microfiber pulp as filler and polyester PP based as matrix. Refined alkaline extracted OPEFB pulp fiber was mixed at different layered composition of the composite of grafted polypropylene. The physical properties and mechanical properties were conducted according to the ASTM standard and showed substantial improvement of the handsheet-molded composite. The scanning electron microgram showed that, as the addition of OPEFB fiber loading increased, there was improved interfacial bonding except for 50% fiber loading which experience fiber pullout. The result also showed improved thermal stability compared with the neat composite. This study will be an effective platform to develop the packaging materials using polymer handsheet composite.